Biomimetic transparent and superhydrophobic coatings: from nature and beyond nature. Issue 10 (18th November 2014) - Yu, Shen; Guo, Zhiguang; Liu, Weimin
Abstract : This review focuses on various promising materials used in fabricating superhydrophobic and transparent surfaces in recent decades. Abstract : It is well known that high optical transparency is one of the most crucial criteria for the overwhelming majority of optical devices and correlative functions, including smart windows, camera lenses, solar cell systems and optoelectronic devices. With the frequent exposure of this equipment to all sorts of environments, such as outdoor conditions, a surface with self-cleaning properties can guard against fouling, humidity, bacterial growth and so forth. That is one type of application of the big family of superhydrophobic coatings. Therefore, integrating high transparency with self-cleaning characteristics is of great importance for such applications. In this review, the recent developments in designing, synthesizing and manufacturing transparent and superhydrophobic surfaces are reviewed. Firstly, the established theoretical aspects of surface wetting properties are summarized and then several natural and bio-inspired superhydrophobic surfaces of diverse microcosmic structures are presented as representative examples. With a focus on distinctively employed materials and the corresponding fabrication of superhydrophobic coatings with high transparency, the promising research directions and application prospects of this rapidly developing field are briefly addressed as well.